"I pulled it out" : a discursive exploration of narrated accounts on decision-making and power differentials in the prescription and use of long-acting reversible contraceptives - Ndabula, Yanela (Rhodes University, Faculty of Humanities, Department of Psychology)
Long-Acting Reversible Contraception (LARC), viz., intrauterine devices, subdermal implants, and injectable contraceptives, are highly effective, long-term birth control methods that limit user action. Alongside the decrease in fertility rates achieved through their mass provision has been their coerced or non-consented administration to marginalised women. These highly effective yet provider-controlled and thus imposable contraceptives have been associated with problematic classed, raced, ageist, and ableist promotions. A critical lens that inquires into their endorsement within clinical practice is thus necessary. The bulk of literature evidencing reproductive injustices in relation to fertility control through LARC technologies emanates from the US and UK contexts. Not much research on the South African context has explored how contraceptive decision-making within clinical interactions shapes LARC uptake despite usage increasing through the years. Using a poststructural, postcolonial feminist framework alongside a reproductive justice stance, this study explores health providers' and contraceptive users' narrations of the prescription and usage of LARC technologies alongside how such talk emplots women who use, continue, or discontinue using these contraceptive technologies. In addition, the power relations (re)produced in the participants' talk that maintain or constrain coloniality and reproductive justice with implications for certain people's reproductive choices/rights were explored. To do so, I used data from 72 semi-structured interviews with contraceptive users (51) and healthcare providers (21). A combination of stratified purposive, convenient, and snowball sampling was used to sample the providers and users of LARC recruited within a city, town, and village. To elicit stories about healthcare providers' and LARC users' narrative emplotments in the prescription and usage decisions about LARC, semi-structured interviewing was used. The questions asked were open-ended and loosely structured around LARC technologies, the decisions that cohere around them, and the makers of those decisions. In analysing the data, I fused Parker's (1992) criteria for locating discourses with Barker's (2017) method for determining the potential for emplotment into narratives. Findings suggest that participants framed contraceptive usage as either a personal, imposed, or shared decision. In personal decisions, the feminisation of contraceptive use emerged, with study, work, and relationship stability statuses requiring participants to solely and prudently self-discipline towards contraceptive uptake so as to match usage with reproduction desire. When decisions were imposed (subtly or openly), a passive role was assumed as female guardians (mothers, grandmothers, or aunts) recommended, pushed, and coerced health users (particularly young women) towards uptake. While the contraceptive users themselves were placed on the margins in decision-making, resisting the imposed decisions was difficult since participants' "risk" of pregnancy was reportedly foregrounded. Shared decisions pointed to less one-sided accounts of decision-making. These decisions were enacted in relationships and were neither siloed nor imposed. Here, sexual partners, parents, or healthcare providers dialogically negotiated contraceptive uptake, and the possibilities for non-use were availed. Data from healthcare providers showed that non-use for young and postpartum women was not an option. In addition, healthcare providers either formed alliances with the LARC users themselves or concerned parents to support or push for contraceptive provision. Supportive alliances enabled secret uptake or ongoing contraceptive usage among some contraceptive users, thus resisting pronatalism or one-sided intentions for childbearing within intimate partnerships. These healthcare providers emplotted themselves as empowering contraceptive users. Alliances that pushed for contraceptive uptake were formed with guardians/parents upon menarche or in case the of rape. In overriding consent within these alliances, healthcare providers avoided being rendered responsible or blameworthy for early pregnancies in the face of the constructed risk used to emplot young women. This over-commitment to providing contraceptives has differing implications for women's sexual agency and sexual health interventions. The data also describe decisions to use contraception as expert-led, patient-led, or collaborative decisions between health users and healthcare providers. Through the information and decision-making was expert-led micro-narrative, a medical discourse constituting use as a necessity and non-use as a risk emerged. A patient autonomy and a my body, my choice discourse informed the information and decision-making was patient-led micro-narrative; here, healthcare providers were either detached or excluded from decision-making as health users assumed more active roles in their own contraceptive care decisions. In collaborative decisions, both parties negotiated (non)use, with LARC users providing their embodied experiences and healthcare providers availing medical knowledge in reaching decisions. The study argues for a reproductive justice framework to underpin the signifier "fertility control" , showing how the threat of degeneration informs responses to reproduction by iii identifying and amplifying deficiency and negative outcomes while masking positive outcomes among certain women. It then creates a fertile ground for the re-engineering and recentring of colonialist thinking and its product, the restraining of the agency of fertile beings it renders "less developed" .
Keywords: Contraception Social aspects -- South Africa; Decision making; Long-acting reversible contraception; Reproductive rights -- South Africa; Control (Psychology); Feminism